Preparation of Lignin-Based Magnetic Adsorbent From Kraft Lignin for Adsorbing the Congo Red - Fang, Lingyan; Wu, Hao; Shi, Yuxuan; Tao, Yuheng; Yong, Qiang (Frontiers in Bioengineering and Biotechnology, 2021)
The utilization of lignin from different lignocellulosic biomass is the hot topic for the biorefinery of biomass. In this paper, magnetic lignin nanoparticles (MLN) were prepared by kraft lignin from bamboo residue and Fe3O4 with different ratio via mannich reaction. The surface morphology and structure of magnetic lignin were characterized and analyzed by X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), which confirmed that the MLN were successfully prepared. The performance of MLN adsorbents was evaluated by adsorbing Congo red solution at different initial concentration and contact time. The results showed that Fe3O4@lignin (1:0.5) had the best adsorption effect on Congo red solution. When the concentration of Congo red reached 0.6g/L, Fe3O4@lignin (1:0.5) had the best adsorption effect on Congo red, reaching 95.5% in only 30 minutes. As lignin is modified by Fe3O4, it can be recovered by magnetic substances after adsorption and has good reuse performance. The results of adsorption kinetics and adsorption isotherm showed that except for the adsorption process of Fe3O4@lignin (1:0.5), which is consistent with the chemical adsorption of the multimolecular layer, the adsorption process of other adsorbents is in accordance with the chemical adsorption of the monomolecular layer. In terms of environmental protection and adsorption efficiency, MLN has become an ideal adsorbent for Congo red dyes due to its simple preparation, superior performance and convenient recovery.